Fatores relacionados à fragilidade multidimensional em pessoas idosas - Faria, Ana; Martins, MM; Laredo Aguilera, José Alberto; Ribeiro, Olga; Almeida Ventura Silva, João Miguel; Faria Fonseca, Esmeralda; Moreira Ferreira, Luciano José (Escola de Enfermagem da Universidade Federal da Bahia, 2022)
Objective: to analyze the sociodemographic and health factors related to multidimensional frailty in elderly people living at home. Method: descriptive, exploratory and cross-sectional study, which evaluated 300 elderly enrolled in a Health Unit in the Northern Region of Portugal. The sociodemographic and health conditions of the old people were analyzed, with application of the Tilburg Frailty Index, Falls Efficacy Scale International – 7 items, Barthel Index and Lawton and Brody Scale. Results: in the elderly in the study, with a mean age of 81.34±6.75 years, frailty was identified in 60.33%. The related factors were: gender, marital status, self-perceived health, pathological history, severe disease in the last year, polymedication, falls, fear of falling and higher level of dependence. Conclusion: multidimensional frailty of the elderly living at home is a prevalent condition. When predictor factors in primary health care are analyzed early, it is possible to intervene in order to delay this syndrome.

Objetivo: analisar os fatores sociodemográficos e de saúde relacionados com a fragilidade multidimensional em idosos que vivem no domicílio. Método: estudo descritivo, exploratório e transversal, que avaliou 300 idosos inscritos numa Unidade de Saúde da Região Norte de Portugal. Foram analisadas as condições sociodemográficas e de saúde das pessoas idosas, com aplicação do Índice de Fragilidade de Tilburg, Falls Efficacy Scale International – 7 itens, Índice de Barthel e Escala Lawton & Brody. Resultados: nos idosos do estudo, com idade média de 81,34±6,75 anos, a fragilidade foi identificada em 60,33%. Os fatores relacionados foram: género, estado civil, autopercepção de saúde, antecedentes patológicos, doença grave no último ano, polimedicação, quedas, medo de cair e maior nível de dependência. Conclusão: a fragilidade multidimensional dos idosos que vivem no domicílio é uma condição prevalente. Quando analisados precocemente os fatores preditores na atenção primária à saúde, é possível intervir de forma a retardar essa síndrome.

Objetivo: analizar los factores sociodemográficos y de salud relacionados con la fragilidad multidimensional en personas mayores que viven en el hogar. Método: estudio descriptivo, exploratorio y transversal, que evaluó a 300 ancianos matriculados en una Unidad de Salud de la Región Norte de Portugal. Se analizaron las condiciones sociodemográficas y de salud de los ancianos, con aplicación del Tilburg Frailty Index, Falls Efficacy Scale International – 7 items, Barthel Index y Lawton and Brody Scale. Resultados: en los ancianos del estudio, con una edad media de 81,34±6,75 años, se identificó fragilidad en el 60,33%. Los factores relacionados fueron: género, estado civil, salud autopercibida, antecedentes patológicos, enfermedad grave en el último año, polimedicación, caídas, miedo a caerse y mayor nivel de dependencia. Conclusión: la fragilidad multidimensional de los ancianos que viven en el hogar es una condición prevalente. Cuando los factores predictores en la atención primaria de salud se analizan temprano, es posible intervenir para retrasar este síndrome.
Factors related to multidimensional fragility in elderly people
Factores relacionados con la fragilidad multidimensional en personas mayores
Keywords: Frailty; Aged; Aging; Nursing